Relación entre los estilos de liderazgo y la calidad del servicio prestado en hoteles categorizados de tres estrellas en el Alto Mayo - 2015 - Ortiz Huaman, Irene (2015)
In the globalization era, customers are increasingly better informed and therefore more demanding with the quality of tourist services consumed. The purpose of this research was to evaluate the relationship between leadership styles and the quality of services in hotels categorized three stars in the Alto Mayo, with the hypothesis that leadership styles influence customer satisfaction, in the host faithfulness and positioning on the tourist market, as an expression of the quality of touristic service. Data were analyzed using SPSS, whose results indicated a predominance of Autocratic Leadership Style, which is characterized by responsible management imposes its will without evaluating the human factor; also it found that overall the quality of services reaches acceptable level, considering that in many of the indicators sticking the label "indifferent". The result of research reveals that there is no direct relationship between leadership styles and the quality of services